2014
DOI: 10.2319/031014-173.1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome assessment of lingual and labial appliances compared with cephalometric analysis, peer assessment rating, and objective grading system in Angle Class II extraction cases

Abstract: Generally, lingual appliances offer comparable treatment results to those obtained with labial appliances. However, care should be taken with lingual appliances because they are more prone to produce uprighted incisors and root angulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…They did find that lingual patients had significantly higher scores in root angulation compared to labial patients [17]. This contrasts with the results of our analysis of OGS subcategories, with only the buccolingual inclination subcategory having a significant difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They did find that lingual patients had significantly higher scores in root angulation compared to labial patients [17]. This contrasts with the results of our analysis of OGS subcategories, with only the buccolingual inclination subcategory having a significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…While the number of studies comparing the quality of treatment outcome between CAD/CAM lingual systems and labial systems is low, our results do agree with a recently published study which also found no overall difference in OGS [17]. Deguchi, et al created matched pairs of 24 lingual patients and 25 labial patients with Class II malocclusions requiring extraction of four premolars.…”
Section: Discussionsupporting
confidence: 90%
“…After reading titles, abstracts, and application of inclusion and exclusion criteria, 87 studies were examined in their full-text forms. From these, 16 studies were deemed eligible for inclusion in the review and for qualitative and/or quantitative synthesis (6,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The flow chart of study selection together with reasons for exclusion is provided in Figure 1.…”
Section: Literature Flowmentioning
confidence: 99%
“…Clinical outcomes of orthodontic treatment can be measured aesthetically and functionally through tooth alignment and occlusion . However, the effectiveness of orthodontic treatment can be difficult to measure or quantify .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes of orthodontic treatment can be measured aesthetically and functionally through tooth alignment and occlusion. [1][2][3][4] However, the effectiveness of orthodontic treatment can be difficult to measure or quantify. 5 Moreover, the treatment outcome may require a long period of time before its effectiveness becomes visually noticeable.…”
Section: Introductionmentioning
confidence: 99%